P-D4 Evaluation of Combination Long-Acting Nanoformulated Antiretroviral Therapy in HIV-1 Infected huPBL NOD.Cg-Prkdcscid Il2rgtm1Wjl/SzJ MICE. (March 2017) - Su, Hang; Dash, Prasanta; Arainga, Mariluz; Edagwa, Benson; Mcmillan, Joellyn; Poluektova, Larisa; Gorantla, Santhi; Gendelman, Howard
Abstract : Early clinical intervention with combination antiretroviral therapy (ART) in human immunodeficiency virus type one (HIV-1) infected people was demonstrated to have sustained benefits by lowering viral set points, protecting CD4+ T lymphocytes and limiting viral reservoir pools. All positive affect long-term patient morbidity and mortality. Notably and as shown in our prior studies cell-targeted nanoformulated ART (nanoART) improves pharmacokinetic and pharmacodynamics profiles and reduces local and systemic drug toxicities in experimental models of HIV/AIDS. These drugs are being considered in a step-wise drug regimen for viral eradication. In the present study, we administrated long-acting nanoformulated combinations of folic acid-decorated cabotegravir, lamivudine and abacavir to human peripheral blood lymphocyte (PBL) reconstituted NOD.Cg-Prkdcscid Il2rgtm1Wjl/SzJ (NSG) mice 24 or 72 hours after HIV-1 infection. Replicate mice received free drugs at equivalent doses. Animals were sacrificed 2 weeks after HIV-1ADA infection. NanoART-treated animals demonstrated 75% recovery of CD4+ T lymphocytes calculated from a total CD3+ cell pool. Immunohistochemical tests showed HIV-1p24+cells (∼80/1000HLA- DR+cells) only in untreated infected animals. NanoART suppressed HIV-1gag RNA expression to <10 copies by real-time RT-PCR in spleen, live, lung, brain and kidney in 90% animals while total viral DNA remained detectable. Limited proviral DNA was seen in nanoART treated animals with plasma viral RNA undetected (<20 copies/mL). Early treatment of combination nanoART in infected PBL mice can effectively suppress HIV-1 growth while preventing CD4+ T lymphocyte loss.